The Impact of Fine Size and Uncertainty on Punishment and Deterrence: Theory and Evidence from the Laboratory - Eberhard Feess; Hannah Schildberg-Hörisch; Markus Schramm; Ansgar Wohlschlegel (Institute for the Study of Labor (IZA), 2015)
We develop a theoretical model to identify and compare partial and equilibrium effects of uncertainty and the magnitude of fines on punishment and deterrence. Partial effects are effects on potential violators' and punishers' decisions when the other side's behavior is exogenously given. Equilibrium effects account for the interdependency of these decisions. This interdependency is important since, in the case of legal uncertainty, higher fines may reduce the willingness to punish, which in turn reduces the deterrence effect of high fines. Using a laboratory experiment, we identify these effects empirically by means of a strategy-method design in which potential violators can condition their behavior on the behavior of potential punishers and vice versa. All our experimental findings on both partial and equilibrium effects are in line with the hypotheses derived from the theory.
Keywords: K14; K42; C91; D64; 330; deterrence; punishment; legal uncertainty; fines; laboratory experiment; partial and equilibrium effects